2020
DOI: 10.47102/annals-acadmedsg.202060
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Options for Patients with Type 2 Diabetes Mellitus during the Fasting Month of Ramadan

Abstract: During Ramadan, Muslims fast from sunrise (Sahur) to sunset (Iftar) and are required to abstain from food and fluids, including oral and injectable medications. Patients with diabetes who fast during Ramadan are at risk of developing hyperglycemia with increased risk of ketoacidosis, hypoglycemia, dehydration and thrombosis. Pre-Ramadan education and preparation of a fasting patient are essential to reduce severe complications. This review paper summarizes studies to date on oral and injectable medications ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…However, the use of newer second-generation sulfonylureas with a lower risk of hypoglycemia, such as gliclazide MR, has increased during this time [10, 28]. In addition, evidence from randomized clinical trials has shown that gliclazide MR is an effective glucose-lowering agent with a very low risk of severe hypoglycemia and with no differences in the risk of mortality or cardiovascular events compared with other classes of glucose-lowering therapies [8, 28]. Although real-world studies have confirmed these results in clinical practice [28], the DIA-RAMADAN study has recently shown that the benefits of using gliclazide MR can also be extended to T2DM patients who fast during Ramadan [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of newer second-generation sulfonylureas with a lower risk of hypoglycemia, such as gliclazide MR, has increased during this time [10, 28]. In addition, evidence from randomized clinical trials has shown that gliclazide MR is an effective glucose-lowering agent with a very low risk of severe hypoglycemia and with no differences in the risk of mortality or cardiovascular events compared with other classes of glucose-lowering therapies [8, 28]. Although real-world studies have confirmed these results in clinical practice [28], the DIA-RAMADAN study has recently shown that the benefits of using gliclazide MR can also be extended to T2DM patients who fast during Ramadan [21].…”
Section: Discussionmentioning
confidence: 99%
“…Ramadan fasting is one of the five pillars of Islam. During Ramadan, Muslims fast from sunrise (Sahur) to sunset (Iftar) throughout the ninth lunar month of the Islamic calendar and are required to abstain from food and fluids, including oral and most of injectable drugs [6, 8]. Although patients with some chronic conditions may be exempt from fasting, the majority of patients with T2DM choose to fast [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Recommendations have been written previously for Muslim patients observing the fasting month of Ramadan. 55,56 Studies have shown that the use of SGLT-2 inhibitors during Ramadan is safe with no major adverse effects and may even result in an improvement in HbA1c. 57 In summary, we suggest that the following modifications be made during the month of Ramadan fasting:…”
Section: Euglycaemic Diabetic Ketoacidosismentioning
confidence: 99%
“…Crucially, the role of SGLT-2 inhibitors has been rarely elaborated in a network meta-analysis to show efficacy in fasting diabetic patients. Currently, most studies have shown that hypoglycemia during Ramadan can be curbed by shifting the therapy from insulin or other oral hypoglycemics to DPP-4 inhibitors or metformin [1,5,6]. A network meta-analysis by Lee et al showed that newer antidiabetics exhibit appropriate glycemic control and lower hypoglycemic complications than sulfonylureas [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, maintaining glycemic control may be difficult, especially for diabetic Muslims who fast during the holy month of Ramadan. [4] Therein lies the major and serious complication of hypoglycemia associated with fasting and oral hypoglycemic antidiabetic such as meglitinides and sulfonylureas [1,5,6]. The Epidemiology of Diabetes and Ramadan (EPIDIAR) demonstrated that around 78.5% of Muslim diabetic patients who fast did not refrain from fasting for at least 15 days.…”
Section: Introductionmentioning
confidence: 99%